Avaliação da prática e a prática da avaliação: desafios ao serviço social na saúde - Igarashi, Nancy Mieko (2012)
The current study Evaluation of Practice and the Practice of Evaluation: Challenges to Social Work in Health Care aims to seize the principal (s) meaning (s) of evaluation for social workers of Social Work, University Hospital, University of São Paulo - HUUSP. Specific objectives are: to discuss trends in health care evaluation, check which evaluation practices are being developed and / or demanded to social workers and describe as the Social Service HU-USP is organized. The motivation for this research arose from the sparse literature on evaluation and practices of evaluation within the Social Services and the perception that the professional category finds difficult to systematize and implement evaluation practices in the actions developed. Trying to understand the meaning of evaluation for social workers and their place in the daily work is that this study was developed. The hypothesis guiding this study is that the evaluation is still conceived as an external instrument, is used to make judgments, pointing errors, to punish and to expose the professional and, for these reasons, takes the place of "non-place" in professional practice. To verify this hypothesis was performed qualitative research, developed from documentary and literature research and field research with social workers from HU-USP. Completed the field survey, the data were systematized and analyzed from the analytical themes that structured this study. The interpretation of data was done in the light of the theoretical and methodological framework, in a reflective dialogue between theory - whose authors are identified in the course of the dissertation - the testimonies of the participants and the reality of professional work. Through this study, it was found that in the collective imagination of the subjects of this research permeates the concept of evaluation as an external action, the authoritarian nature, not participatory, causing fears, anxieties and resistances. On the other hand, there is also the idea that the evaluation has its importance since it can be participatory and democratic, when its objective is not to blame people, but the improvement of the action performed. In this sense, participants in the study showed the consequences of not having a systematic evaluation of the work and pointed out how it would be built. This study confirmed the initial hypothesis, besides allowing an initial approach between the assessment in theoretical perspective and evaluation in the practical field of Social Work in Health Care